A clinicopathological study and management of abdominal tuberculosis - Majji, V. V. Harika; Erabati, Santosh Raja; M., Swetha B. (International Surgery Journal, 2020)
Background: Tuberculosis is a major health problem in developing countries. Inspite of considerable advances, abdominal tuberculosis still continues to be of paramount health issue in India, owing to its vague and non-specific presentation challenging the therapeutic skills of present day surgeon. Surgical intervention was frequently used in the past for diagnosis is not necessary and is reserved for complications like obstruction, perforation, fistula, or a mass which does not resolve with medical therapy. Methods: 30 patients admitted in Department of Surgery satisfying the inclusion criteria from November 2015 to October 2017. Patients were selected on a prospective basis. Results: In this study out of 30 patients, 16 patients were treated conservatively with anti- tubercular therapy (ATT) alone and 14 patients underwent surgical treatment. Out of 14 patients, 5 patients were operated on emergency basis and 9 were operated electively. Of the 5 emergency cases, 2 patients underwent resection anastomosis of small bowel, 1 patient underwent adhesiolysis, and 3 patients with hollow viscus perforation underwent perforation closure with peritoneal drainage. Conclusions: Tuberculosis has become a resurgent global problem with increasing numbers of extrapulmonary manifestations, non-specific features of abdominal tuberculosis result in difficulty in establishing a diagnosis, hence prompt initiation of treatment that can be either medical management or a surgical procedure is important to prevent morbidity and mortality associated with it.